The world of psychology - Wood, Samuel E.; Wood, Ellen R. Green (Allyn and Bacon, 1999)
New edition of an introductory text suitable for both advanced placement high school- and college-level students. Coverage includes biology and behavior, sensation and perception, states of consciousness, learning, memory, cognition and language, intelligence and creativity, child development, adolescents.